Biomechanical analysis of spinal range of motion and intervertebral disc loadings in normal and adolescent idiopathic scoliosis models - Wang, Haikuan; Ma, Zhengwei; Wu, Zhihua; Lin, Yuanfang; Yu, Jie; Qian, Xin; Jian, Sili; Sun, Yueli; Wei, Wei; Yu, Xiang; Liang, Ziyang (Frontiers in Bioengineering and Biotechnology, 2025)
ObjectiveWhile the Lenke classification enhances our structural understanding of adolescent idiopathic scoliosis (AIS), the biomechanical implications for spinal range of motion (ROM) and intervertebral disc (IVD) loadings remain unclear. This study aims to quantitatively explore and compare these biomechanical responses in normal thoracolumbar spines and those with various curvatures of Lenke types under pure bending conditions.MethodsThe baseline thoracolumbar finite element (FE) model was derived from a comprehensive human body FE model, validated, and calibrated against spinal responses under dynamic compression and quasi-static bending conditions. Using mesh morphing, AIS models of Lenke 1, Lenke 2, Lenke 3, and Lenke 5 were established to represent their respective spinal curvatures. Pure bending moments of ±7.5 Nm in flexion-extension, lateral bending, and axial rotation were applied to both normal and AIS models. Global spinal ROM and ROM of spinal segments T1-T6, T7-T12, and L1-Sacrum were measured under each loading condition. IVD mechanical loadings, including force, moment, and VonMises stress, were also evaluated and compared across all models.ResultsAIS models showed higher principal ROM compared to the normal model, with Lenke 2 having the highest ROM from T1-Sacrum and Lenke 3 the highest ROM from T6-12. AIS models exhibited more asymmetry in segmental ROM, particularly in the lumbar spine during lateral bending and axial rotation. IVD mechanical loadings varied significantly between normal and AIS models, influenced by spinal curvature types. AIS models had higher secondary moments and shear forces, especially under flexion-extension. The highest stress was mostly observed in the frontal IVD regions under flexion which was greatly reduced under extension. Lateral bending caused the highest stress predominantly on the same side as the loading direction in the IVD regions. The IVDs of T6-T7 and T12-L1 showed even stress distribution under axial rotation, while the right IVD regions of L5-Sacrum sustained the highest stress under right axial rotation, and the left regions under left axial rotation. In Lenke 3 and Lenke 5 models, the right (concave) regions of the T12-L1 IVD consistently sustained higher stress levels, regardless of the loading conditions applied.ConclusionThis study underscores significant biomechanical differences between normal and AIS models, revealing intricate interactions within scoliotic spines and enhancing our understanding of AIS biomechanics. These insights can aid in better diagnosis, treatment planning, and prognosis. Extension-focused therapeutic exercises may reduce stress on anterior IVDs, potentially lowering the risk of low back pain or disc herniation, while careful management of rotational exercises can help minimize stress in the lower lumbar regions.